PENGARUH FAKTOR BAURAN PEMASARAN TERHADAP PERTIMBANGAN NASABAH MEMILIH BANK SYARIAH DI KOTA MEDAN - Firman - Yulianto K.; Agung - Yuniarinto; Surachman - - (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT The expansion of syari’ah bank in Indonesia recently can be concluded to have a significant development, it also take a large number of attention from the Indonesian goverment though Indonesian central Bank, Bank Indonesia in monitoring the development of syari’ah bank industry. Consumers behaviour toward syari’ah bank, which is shown by a variety respon. Consumer consideration in choosing syariah bank, has become a very interesting topics to be discuss in knowing the information on how far does Indonesian people interest with syari’ah bank and what kind of factors can affect the community to deal with syari’ah bank by being the customer of syariah bank. One of the factors is marketing mix strategy which the company, syari’ah bank, has formulated. The purpose of this research is to analize the effect of marketing mix, which are product, price, promotion, place, people, process, and physical evidence, towards customer consideration in choosing syariah bank. And also to inform which the most dominant factor from the all seven factors to be consider by customer. The field research is the city, Medan, with population all of Medan’s syariah bank individual customer, through, Bank Syariah Mandiri, Medan Branch Office; Bank Muamalat Indonesia, Medan Branch Office; BNI Syariah, Medan Branch Office, using purposive sampling method, with 100 number of respondents in finishing the survey. Hypothesis examination involves mutiple regression analysis. Result indicates only three of seven marketing mix factors, which are product, place, and people has significantly affect customer consideration in choosing syariah bank in Medan. The other four factors, price, promotion, process, and physical evidence does not significantly affect customer consideration. The one factor gives the most dominant consideration is the product. Keywords: Syari’ah Bank, marketing mix